ANALISIS NILAI WASTE KERAMIK PADA PROYEK X - Mathew, Kevin; Waty, Mega (JMTS: Jurnal Mitra Teknik Sipil, 2024)
Construction projects often produce values, in the construction field can be interpreted as a loss or a loss of material resources, time, and capital, which is caused by activities that cost money, directly or indirectly, but does not add value to end product for users of construction services. The values produced in the form of materials, quality, time, and costs. In this research, will be examined ceramic, where ceramics often have a significant effect and can influence project costs. Therefore, this research aims to optimize the value of ceramic on project x to optimize costs to reduce its value. The method that will be used in this research is the method of observation, interviews, and analysis of calculations through working drawings, calculations that will be carried out using 2 methods to determine the difference of values so that the value that is expected to be the optimum value for use. This optimization value is very important because the project location is outside Java, and the material supply is on the island of Java so that it can reduce material delivery costs which are quite expensive and can affect the project budget. Keywords: residual value; building project; level of residual value; residual value of ceramics Abstrak Proyek konstruksi serinng kali menghasilkan nilai waste, nilai waste yang di hasilkan dapat berupa waste material,mutu,waktu,hingga biaya. Namun pada penelitian ini nilai waste yang akan di teliti adalah waste keramik dimana keramik seringkali memberikan efek signifikan dan dapat mempengaruhi biaya proyek, oleh karena itu pada penelitian ini bertujuan untuk mengoptimalkan nilai waste keramik pada proyek x agar dapat mengoptimalkan biaya pada proyek hingga berkurang nya nilai waste keramik yang mempunyai dampak negative pada lingkungan sekitar proyek.metode yang akan di gunakan dalam penelitian ini adalah metode pengamatan pada lapangan, wawancara,serta Analisis perhitungan melalui gambar kerja, perhitungan yang akan dilakukan dengan 2 metode yang berbeda untuk mengetahui perbandingan nilai waste sehingga didapatkan nilai yang diharapkan menjadi nilai optimum untuk penggunaan waste. Nilai optimasi ini sangat penting dilakukan dikarankan lokasi proyek yang berada diluar pulau jawa dan supply material berada dipulau jawa sehingga dapat mengurangi biaya pengiriman material yang cukup mahal dan dapat mempengaruhi anggaran proyek